2013
DOI: 10.1177/1094670513478832
|View full text |Cite
|
Sign up to set email alerts
|

IT Capability for Health Care Delivery

Abstract: In recent years, there has been a proliferation of health information technologies (HITs) that promise to improve the delivery of care. Health care service providers are faced with an increasing push to develop electronic medical record (EMR) capability, which is the ability to leverage health IT to enable and link the clinical processes for an effective and efficient delivery of care. However, there is little guidance in the literature on the performance implications of EMR capability and whether providers sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 84 publications
(163 reference statements)
2
20
0
Order By: Relevance
“…Liu et al (2011) examined the e-healthcare maturity in Taiwan hospitals and was able to show that hospitals with higher levels it IT maturity had lower costs. Dey et al (2013) studied the EMR system capabilities within 1,011 acute care facilities in the US and found that hospitals with higher EMR capabilities had higher operational performances.…”
Section: It Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2011) examined the e-healthcare maturity in Taiwan hospitals and was able to show that hospitals with higher levels it IT maturity had lower costs. Dey et al (2013) studied the EMR system capabilities within 1,011 acute care facilities in the US and found that hospitals with higher EMR capabilities had higher operational performances.…”
Section: It Maturitymentioning
confidence: 99%
“…Liu et al (2011) examined the e-healthcare maturity in Taiwan hospitals and its impact on financial performance. While some of these studies (Dey et al, 2013;Jaana et al, 2005;Pare & Sicotte, 2001) have looked at the IT capabilities of healthcare organizations, they did not examine how the organizations have matured through their use of IT. Also, these studies have focused on large organizations such as hospitals and have ignored SPP.…”
Section: Introductionmentioning
confidence: 99%
“…Technology is expected to facilitate the cost-effective provision of social care services both in administrative and managerial processes and in care practice (DoH, 2005). Despite the millions spent on researching healthcare IT, the research community has yet to agree whether information systems (IS) will make healthcare more seamless, efficient, patientcentered and safe, or more fragmented, time-consuming, technology-centered, and risky (Baines, Wilson, & Walsh, 2010;Dey, Sinha, IT adoption in social care: A study of the factors that mediate technology adoption* & Thirumalai, 2013;Greenhalgh & Stones, 2010;Petrakaki, Barber, & Waring, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Venkatraman Bala, Venkatesh, and Bates (2008) defined anEMR as an "automated clinical system that generally includes data related to medical history, patient demographics, clinician's notes, drug information, electronic proscriptions and diagnostic test orders" (p. 140). In theory, EMRs are designed to follow a patient with no regard for location (Dey, Sinha, & Thirumalai, 2013;Williams & Boren, 2008;). For example, the primary care physician and any number of specialists can review a patient's EMR even if these physicians are located in different states.…”
mentioning
confidence: 99%